IN VITRO EVALUATION OF ANTIFUNGAL ACTIVITY OF SELECTED MALAYSIAN PLANTS AGAINST THE WILT PATHOGEN OF BANANA, Fusarium oxysporum f.sp. cubense TROPICAL RACE 4 - Paramalingam, Pavitra; Kheiril Anuar, Muhammad Salahudin; Akmal Baharum, Nadiya; Abdullah, Janna Ong; Abd Aziz, Julia; Saidi, Noor Baity (Malaysian Journal of Science, 2021)
Fusarium wilt of banana is one of the most serious diseases affecting banana plantations worldwide. In this study, the inhibitory activities of four essential oils (clove, cinnamon, lesser alpinia and eucalyptus) and five hydrosols (kaffir lime, eucalyptus, bitter ginger, fig and tea tree) on the in vitro growth of the causal agent of the disease, Fusarium oxysporum f. sp. cubense Tropical Race 4 (TR4), were investigated. Results showed that some of these plant extracts inhibited the in vitro mycelial growth of TR4 in a dose-dependent manner. Clove oil and tea tree hydrosol were the most effective in suppressing mycelial growth in this study, the with percentage inhibition radial growth (PIRG) recorded at 46% and 69%, respectively, while lesser alpinia oil and kaffir lime hydrosol showed moderate inhibition of mycelial growth with the PIRG of 33% and 64%, respectively. These results suggest that these compounds have the potential to be used in future greenhouse studies as a single treatment or in combination with previously established biological control agents against Fusarium wilt of banana.